Microplasma synthesized gold nanoparticles for surface enhanced Raman spectroscopic detection of methylene blue. Issue 2 (17th November 2021) - Li, Xuanhe; Lin, Liangliang; Chiang, Wei-Hung; Chang, Kuan; Xu, Hujun
Abstract : Surface enhanced Raman scattering (SERS) is a powerful and sensitive spectroscopic technique that allows for rapid detection of trace-level chemical species in a non-invasive and non-destructive manner. Abstract : Surface enhanced Raman scattering (SERS) is a powerful and sensitive spectroscopic technique that allows for rapid detection of trace-level chemical species in a non-invasive and non-destructive manner. In the present work, high purity crystalline AuNPs were fabricated by a one-pot microplasma-induced approach, which were then used to decorate silicon substrates to prepare SERS substrates via an immersion method. Complimentary characterizations have been performed to examine the AuNPs as well as the AuNP-decorated SERS substrates, including UV-vis, TEM, HRTEM, SAED, SEM, and XRD. Methylene blue (MB) was selected as the probe analyte to further examine the SERS properties of the silicon substrates. Results show the AuNP-decorated SERS substrates offer excellent reproducibility and significant enhancement of Raman features, allowing the detection of extremely low concentration MB molecules that could not be detected using the bare silicon substrate. A linear relationship was established between SERS intensity and MB concentration from 10 −11 to 10 −5 M, with a detection limit of 10 −11 M and an enhancement factor (EF) of 1.06 × 10 8 at the optimum condition. The reusability of the SERS substrates was also evaluated by Raman detection of MB molecules using the substrates after different times of usage, demonstrating good recyclability. Furthermore, the SERS substrates exhibit remarkable versatility through the analysis of different analytes like crystal violet, rhodamine B, methyl red, methyl orange, and neutral fuchsin.